إجراء النظام إدارة التعلّم "التلخيص" لواسطة التعليم اللغة العربية في الجامعة الإسلامية الحكومية بكالونجان - Faliqul Isbah; Muhamad Jaeni; Muhammad Ulil Fahmi (Imtiyaz : Jurnal Pendidikan dan Bahasa Arab, 2021)
Online learning media used by lecturers in lectures requires them to provide several links to materials and assignments to students. The number of links provided has the potential to cause difficulties for students to store, remember and access these links. This study aims to explain the creation and use of the At-Talkhis Learning Management System (LMS) for learning Arabic. This research method uses the agile method, which is one method that is quite popular today because it offers flexibility, so the author can return to an earlier phase if any changes are needed. The results of this study are the process of making At-Talkhis using hyperlinks on MS Power Point to create a format (Portable Document Format), how to use it and the results of the student response survey, based on the survey results 98.7% of students gave a positive response to the use of At-Talkhis. in Arabic courses. The advantage of At-Talkhis is that it is easy to use because its features are common, cheap because the features are free for the public and can be added with various other media to support Arabic learning. the disadvantages of At-Talkhis are internet signal constraints, not all lecturers can make attractive designs and difficulties in compiling what features will be included in the Learning Management System.